Use of assisted reproductive technology to reduce the risk of transmission of HIV in discordant couples wishing to have their own children where the male partner is seropositive with an undetectable viral load. Issue 6 (8th December 2003) - Baker, H W G; Mijch, A; Garland, S; Crowe, S; Dunne, M; Edgar, D; Clarke, G; Foster, P; Blood, J
Abstract : The advances in treatment of HIV and the introduction of polymerase chain reaction assay for the virus now make it acceptable for HIV discordant couples where the male partner is seropositive to attempt to conceive through artificial insemination by husband (AIH) or via in vitro fertilisation. With undetectable viral load and washed sperm, there is minimal risk of transmission of HIV to the female partner, children, other patients, or staff. We describe the development of a programme of AIH for HIV discordant couples and the reasoning behind offering such a programme.